Suspended Particulates Concentration (PM10) under Unstable Atmospheric Conditions over Subtropical Urban Area (Qena, Egypt) - M. El-Nouby Adam (Advances in Meteorology)
The main purpose of this study is to evaluate the suspended particulates (PM10) in the atmosphere under unstable atmospheric conditions. The variation of PM10 was investigated and primary statistics were employed. The results show that, the PM10 concentrations values ranged from 6.00 to 646.74 μg m−3. The average value of PM10 is equal to 114.32 μg m−3. The high values were recorded in April and May (155.17 μg m−3 and 171.82 μg m−3, respectively) and the low values were noted in February and December (73.86 μg m−3 and 74.05 μg m−3, respectively). The average value of PM10 of the hot season (125.35 × 10−6 g m−3) was higher than its value for the cold season (89.27 μg m−3). In addition, the effect of weather elements (air temperature, humidity and wind) on the concentration of PM10 was determined. The multiple R between PM10 and these elements ranged from 0.05 to 0.47 and its value increased to reach 0.73 for the monthly average of the database used. Finally, the PM10 concentrations were grouped depending on their associated atmospheric stability class. These average values were equal to 122.80 ± 9 μg m−3 (highly unstable or convective), 109.37 ± 12 μg m−3 (moderately unstable) and 104.42 ± 15 μg m−3 (slightly unstable).